The Effect of Circuit Core Stability Training Towards The Strength of Abdominal Muscles and Balance - Luh Putu Tuti Ariani (Budapest International Research and Critics University, 2021)
Several aspects affect an athlete’s improvement in achievements, such as physical, technical, strategical, and psychological aspects. One of the physical aspects observed in this research is circuit core stability training. This research aims to find out the use of interval 1:1 and interval 1:2 of the circuit core stability techniques towards the improvement of abdominal muscles’ strength and balance. This research uses the randomized pre and post-test design. The sample was 20 students of the Sports Training and Education study program, Surabaya State University. The abdominal muscles strength is tested by doing 30 minutes sit-up, while the balance is tested through Balance Beam Test. The result of the homogeneity test shows that the samples are normal and homogeneous. Paired sample T-test is used to find out the mean among the samples. The circuit core stability training is done in 18 meetings, pre-test and post-test are done before and after the treatment. It is found that the circuit core stability test can improve the abdominal muscles' strength and balance. The result shows the improvements before and after the treatment. It is found that there is improvement in average abdominal strength from 22,4 to 24,2, and balance from 39.5 to 42.8 seconds in the core stability 1:1 group. Meanwhile, in the core stability 1:2 group, it was found that there is an improvement of abdominal muscles strength from23.4 times, to 25.2 times. The balance test shows that there is improvement in the average from 79 to become 85,40 seconds. From the result, it can be concluded that circuit core stability 1:1 and 1:2 can significantly improve the strength of the abdominal muscles and balance.